2009
DOI: 10.1080/15299710903316653
|View full text |Cite
|
Sign up to set email alerts
|

Bisexuals in Relationships: Uncoupling Intimacy from Gender Ontology

Abstract: A dominant notion that homosexuality and heterosexuality give meaning to bisexuality already exists. But no one has explored the meaning that bisexuality might accrue with regard to monosexuality. Because bisexuals were never fully recognized within queer theory, the homosexual-heterosexual binary opposition continues to be the primary understanding of difference. Further, within queer theory, the idea of intimacy seems to be attributed to a gendered ontology, that is, the regulation of gender representation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
55
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(58 citation statements)
references
References 4 publications
1
55
0
2
Order By: Relevance
“…However, it did not become a definer of the couples' relationships, and no such thing as a clear cut bicouple discourse was identified. Bisexuality did thus not appear as central as in other interview studies on bisexuality (Gustavson, 2009;Hayfield et al, 2014;Kangasvuo, 2011). Instead, the bisexual women and their partners made their relationships intelligible by taking up positions in the discourse of the enduring couple relationship.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…However, it did not become a definer of the couples' relationships, and no such thing as a clear cut bicouple discourse was identified. Bisexuality did thus not appear as central as in other interview studies on bisexuality (Gustavson, 2009;Hayfield et al, 2014;Kangasvuo, 2011). Instead, the bisexual women and their partners made their relationships intelligible by taking up positions in the discourse of the enduring couple relationship.…”
Section: Discussionmentioning
confidence: 73%
“…Not without tension: bisexuals often wish to challenge the notion of bisexuality as nonmonogamous by necessity, but many also explore relational constellations other than normative exclusive relationships (Gustavson, 2009;Kangasvuo, 2011;McLean, 2004;Rust, 1996). Equating this with an assumption that bisexuals will always cheat on their partners, or that they are not capable of long-term commitment, is problematic (Kangasvuo, 2014;McLean, 2004).…”
Section: Bisexuality In a Relationshipmentioning
confidence: 97%
“…A small body of literature, mainly outside the United Kingdom (U.K.), has specifically focused on bisexual relationships (e.g., Bradford, 2012;Feinstein, Latack, Bhatia, Davila & Eaton, 2016;Gustavson, 2009;Lahti, 2015;Li et al, 2013). Bisexual participants are seemingly aware of notions that they must simultaneously be in relationships with men and women and some have challenged this idea (Bradford, 2004a;Gustavson, 2009;Li et al, 2013). While monogamous relationships may be understood as an easy option due to their social acceptability, monogamous bisexual people have reported feeling that they have had to forego an aspect of their identity (McLean, 2007), and that their bisexuality is invisible (Robinson, 2013).…”
Section: Recent Research On Bisexual People's Relationshipsmentioning
confidence: 99%
“…This can include bisexual people having difficulty in finding partners willing to be (or stay) with them (Li et al, 2013). Bisexual people's partners have been critical of their partner's bisexuality in ways which directly link to negative conceptualisations of bisexual identities (Gustavson, 2009;Li et al, 2013). Additionally, some bisexual women have felt objectified by their male partners (Li et al, 2013).…”
Section: Recent Research On Bisexual People's Relationshipsmentioning
confidence: 99%
“…The number of studies has shown a sharp increase since the 2000s and deal with a plethora of topics such as identification, stereotyping, negotiating compulsory coupledom, and more. The Journal of Bisexuality in particular has been an important outlet for studies on bisexuality and relationships (e.g., Anderson, Scoats, & McCormack 2015;Armstrong & Reissing, 2014;Gustavson, 2009;Kangasvuo, 2011;Klesse, 2011;McLean, 2004;Pennington, 2009), but several studies were published in other journals such as Christian Klesse's twin publications on polyamory and nonmonogamies in bisexual people (Klesse, 2005(Klesse, , 2006, Annukka Lahti's (2015) article on Finnish bisexual women's negotiations of discourses on romantic love and sameness to heterosexual couples, and Renate Baumgartner's (2017) recent article on Austrian bisexual women's internalized binegativity regarding relationship options and stereotypes.…”
Section: Bisexuality and Relationshipsmentioning
confidence: 99%